FORMATION OF A RATIONAL ROUTE NETWORK FOR DELIVERY OF CONTAINERIZED CARGOES (Transport systems and technologies, 2021)
The formation of a rational route network contributes to the timely and uninterrupted delivery of products and more efficient interaction of supplier organizations, recipient organizations and trucking organizations. However, at present, the issues of increasing the level of customer service, which in market conditions are closely related to the problem of service and quality of service, are becoming increasingly important. The quality of transportation should be understood as the ability of the trucking industry to meet the needs of enterprises and the public in transport services with minimal costs. Thus, there is a question of forming a rational route network, which would improve the qualityof customer service with minimal costs. The use of economic and mathematical methods and information technologies in the formation of a rational route network allows to obtain a synergistic effect, namely by reducing overall costs, improve the quality of service. The formation of a rational route network according to the proposed algorithm allows to determine the cost of delivery of goods and the level of service of cargo owners with the specified number of dispatchers and cars at the enterprise and provide companies with practical recommendations on the number of dispatchers and cars needed to meet customer needs. service.
Keywords: route network, consignor, consignee, containerized cargo, regression model, total costs, quality level.